Development of service sensor tools on table tennis net - Firdaus, K.; Mario, D. T. (Journal of Physical Education and Sport, 2022)
Service in table tennis is one of the important indicators to rely on for winning the competition. However, nowadays coaches or referees do not have an accurate instrument to assess the service in table tennis due to the limitation of supporting tools like sensor technology. This research is the research and development and intends to develop a service sensor tool on a table tennis net that can be used for learning or during table tennis matches. Also, it aims to produce a product and test its effectiveness. Four stages guide such process, that is tool design, circuit making, program development, and tool testing. We used the adapter 220 v (12 Vdc) 2A, Arduino Uno, SW 420 vibration sensor, step down DC-DC voltage drop, and 1 ch relay driveras the material. These afore mentioned components were designed, assembled,and both programmatically and physically installed on the table tennis net. After going through all steps, the new tool was validated by different experts, mainly electrical engineering experts, table tennis experts, and table tennis referees in the wake of determiningits weaknesses and usefulness. Then, it underwent field trials on table tennis athletes who competed atthe regional level for sports week events in West Sumatra, Indonesia. Results of the expert validity test obtained 89.81 or very good category. Besides, the results of field trials show that the service sensor detects all service balls especially when they touch the net. Based on the data harvested, the results of the tool's reliability test were very high. That said, the tool can accurately, objectively, easily, and practically assess and also be used in learning or during table tennis matches to make it easier for assessing performance and services.